Phytochemicals and medicinal properties of indigenous tropical fruits with potential for commercial development - Khoo, Hock Eng; Azlan, Azrina; Kong, Kin Weng; Ismail, Amin (Hindawi Publishing Corporation, 2016)
Hundreds of fruit-bearing trees are native to Southeast Asia, but many of them are considered as indigenous or underutilized. These species can be categorized as indigenous tropical fruits with potential for commercial development and those possible for commercial development. Many of these fruits are considered as underutilized unless the commercialization is being realized despite the fact that they have the developmental potential. This review discusses seven indigenous tropical fruits from 15 species that have been identified, in which their fruits are having potential for commercial development. As they are not as popular as the commercially available fruits, limited information is found. This paper is the first initiative to provide information on the phytochemicals and potential medicinal uses of these fruits. Phytochemicals detected in these fruits are mainly the phenolic compounds, carotenoids, and other terpenoids. Most of these phytochemicals are potent antioxidants and have corresponded to the free radical scavenging activities and other biological activities of the fruits. The scientific research that covered a broad range of in vitro to in vivo studies on the medicinal potentials of these fruits is also discussed in detail. The current review is an update for researchers to have a better understanding of the species, which simultaneously can provide awareness to enhance their commercial value and promote their utilization for better biodiversity conservation.